Quantitative lipoxygenase product profiling by gas chromatography negative-ion chemical ionization mass spectrometry - Lehmann, Wolf-Dieter; Metzger, Karl; Stephan, Michael; Wittig, Ulrike; Zalán, Ildikó; Habenicht, Andreas; Fürstenberger, Gerhard (Analytical biochemistry, 1995)
An assay for the quantitative determination of the hydroxylation profile of long-chain fatty acids is described for gas chromatography negative-ion chemical ionization mass spectrometry and stable isotope dilution using [carboxyl-18O2]-labeled internal standards. The assay has been applied to the study of fatty acids isolated from body fluids, tissue, and cultured cells. Examples for the analyses of biological systems expressing 5-, 8-, 12-, or 15-lipoxygenase activity are given and the most important sources of analytical errors are addressed. Increased specificity compared to analysis by negative-ion chemical ionization, at the cost of sensitivity, can be achieved by the use of positive-ion electron impact ionization for the investigation of hydrogenated pentafluorobenzylester/trimethylsilylether derivatives. The method described provides complete, specific, and quantitative profiles of hydroxylated fatty acids originally present in biological samples or generated in vitro by incubation with polyunsaturated fatty acid substrates such as linoleic or arachidonic acid.
Elektronische Reproduktion der Druck-Ausgabe 25. Mai 2002
Gesehen am 21.05.2025